Integrated Buddhism for Healing and Uplifting for vulnerable persons Vulnerable Groups through the Elderly Network in Loei Province - Phiriyasuvat, Jarukit; Singudom, Thongchai; Narinto, Phra Taweesak; warakron,Dr., Phrakrusutakun; phothiwong, Phrakhru Pariyatthi (MCU Haripunchai Review, 2026)
This research aimed to 1) study the healing and upliftment of vulnerable groups through the elderly network in Loei Province, 2) develop the healing and upliftment of vulnerable groups through the elderly network in Loei Province, and 3) evaluate the healing and upliftment of vulnerable groups through the elderly network in Loei Province. Qualitative research included interviews with 64 key informants, elderly people and socially vulnerable people, and 8 focus group discussions. The research tools included interview forms and focus group discussions. Content analysis was used. The results of the study revealed that: 1) The healing and uplifting of vulnerable groups through the elderly network in Loei Province revealed (1) physical health promotion through appropriate physical activity; (2) mental health through mindfulness meditation; (3) emotional health through loving-kindness meditation to reduce stress; and (4) social health, the network played a role. "Dhamma Mentors" 2) Developing healing and uplifting for vulnerable groups through the Elderly Network in Loei Province. The program was developed for each vulnerable group: (1) Physical: Assisting the elderly in need through the Friends Helping Friends project; (2) Mental: Promoting self-worth through Buddhist activities; (3) Emotional: Organizing recreational activities and field trips to reduce loneliness and depression; and (4) Social: Promoting participation to reduce family burdens and health care costs. 3) An evaluation of healing and uplifting for vulnerable groups through the Elderly Network in Loei Province revealed that while attention is given to caring and observing daily life patterns, both physical and mental, excessive assistance can lead to the elderly not being able to utilize their full potential. Consultation with experts and physical and mental health rehabilitation are also provided.